Gynecologic Cancer InterGroup (GCIG) Consensus Review for Mullerian Adenosarcoma of the Female Genital Tract. (1st November 2014) - Friedlander, Michael Leonard; Covens, Alan; Glasspool, Rosalind M.; Hilpert, Felix; Kristensen, Gunnar; Kwon, Sanghoon; Selle, Frederic; Small, William; Witteveen, Els; Russell, Peter
Abstract : Mullerian adenosarcomas of the female genital tract are rare malignancies, originally described in the uterus, the most common site of origin, but they may also arise in extrauterine locations. Uterine adenosarcomas make up 5% of uterine sarcomas and tend to occur in postmenopausal women. They are usually low-grade tumors and are characterized by a benign epithelial component with a malignant mesenchymal component, which is typically a low-grade endometrial stromal sarcoma but can also be a high-grade sarcoma. Tumors that exhibit a high-grade sarcomatous overgrowth have a worse outcome. Adenosarcomas have been described as being midway along the spectrum between benign adenofibromas and carcinosarcomas. They generally have a good prognosis with the exception of deeply invasive tumors or those with high-grade sarcomatous overgrowth. Extrauterine adenosarcomas also have a higher risk for recurrence. In view of their rarity, there have not been any clinical trials in mullerian adenosarcomas and relatively little research. This article reviews the current knowledge and provides recommendation for the management of mullerian adenosarcomas.